Bunkers are no longer significant in voyage calculations with the low bunker prices, are bunkers still a major consideration for voyage calculations? (With focus on tanker sector) - Yong, Michele Cai Jie (2017)
Bunker cost has always taken up a major proportion of voyage cost due to high bunker price. The recent drop in crude oil price has led to a fall in bunker price, thus reducing bunker cost for vessels. Other factors that affect bunker cost are the speed and condition of the vessel as well as the routes or distance that the vessel sails through. There is a need to find out whether bunker cost is still a major consideration when operating a vessel such that the owner will be able to devise appropriate strategies which allow for profit maximisation. This paper aims to determine whether bunker cost remains the major consideration of voyage calculations for tankers given the low bunker price. The individual components of voyage costs were analysed to determine whether any of them now take over bunker cost as the major voyage cost. Through interviews with industry professionals and research papers, it is found that port cost is likely to take over bunker cost as the major cost if the voyage performed by the vessel is short and port cost is relatively more expensive. Similarly, canal dues would also take up a larger proportion of the voyage cost given the low bunker price as canal dues are an inevitable cost due to time limitations. This reduces the significance of bunker cost in voyage calculations. While bunker cost has been significant in voyage calculations, other performance measures like improving turnaround time is important as well even though it results in higher bunker cost. Second, the tanker market condition of low freight rates has resulted in vessels sailing at economical speed instead of slow steaming such that more trips can be completed with the time saved, increasing profit. Third, the type of contract, voyage or time charter will also affect the significance of bunker cost on the different stakeholders. It is found that low bunker price has resulted in lower premiums for fuel efficient vessels and this proves that the demand for fuel efficient vessels is lower in times of low oil price. All of the above factors show that less emphasis is placed on bunker cost when bunker price is low. On the other hand, companies still constantly engage in hedging even with low bunker price have removed the risk of fluctuation in bunker price. This demonstrates the notion that bunker price remains relevant no matter the price. All in all, bunker cost is still a major consideration for voyage calculations albeit it becoming less significant. However, in the long run, if the low freight market and low bunker prices were to stay, the reverse may be true instead as the marginal savings on bunkers are decreasing. There is, therefore, a need for companies to search for alternative measures to reduce total costs instead.